Seed systems and markets: Reflection on progress and political economy - Spielman, David J. (International Food Policy Research Institute, 2021)
Over the past two decades, seed systems and markets in many sub-Saharan African countries have become a central topic in the public discourse around agricultural development. The issues are complex, and often shaped by the specific nature of the crop itself, the agroecology it is cultivated in, and the channels through which farmers obtain seed. What attracts less attention are the political economy factors that shape seed systems development. Not since an array of scholars working with the Institute of Development Studies published a deep and thoughtful volume on the Politics of Seed in Africa’s Green Revolution has the topic of political economy received such attention.